Performance and design of InGaAs /InP photodiodes for single-photon counting at 1.55 microm. - Hiskett, P; Buller, G; Loudon, A; Smith, J; Gontijo, I; Walker, A; Townsend, P; Robertson, M (2000)
The performance of selected, commercially available InGaAs/InP avalanche photodiodes operating in a photon-counting mode at an incident wavelength of 1.55 microm is described. A discussion on the optimum operating conditions and their relationship to the electric field distribution within the device is presented.